ILRI Corporate Report 2009-2010. Back to the Future: Revisiting Mixed Crop-Livestock Systems - International Livestock Research Institute (International Livestock Research Institute, 2010)
This corporate report looks ‘back to the future’—to the thousand million farmers practicing small-scale mixed crop-and-livestock agriculture in poor countries—the kind of seemingly old-fashioned family farming systems that have become so fashionable in recent years among those wanting to reform the industrial food systems of rich countries.